Towards understanding the effects of stocking density on farmed South African abalone, Haliotis Midae,Towards understanding stocking density of farmed South African abalone Haliotis midae - Nicholson, Gareth Hurst (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The profitability of abalone farms is heavily influenced by their production per unit of grow-out space. With farms having physically expanded to the maximum, and with increasing production costs, one of the most realistic ways for farms to increase their production is through optimizing stocking densities. The effect of stocking density on Haliotis midae performance is undocumented and optimal stocking densities for this species have not been determined. Experiments were conducted under farm conditions to investigate the effects of four different stocking densities (16 %, 20 %, 22 % and 24 % of available surface area) on growth, production and health of three different size classes of abalone (15-35 g, 45-65 g, and 70-90 g start weight). Each treatment was replicated four times and trials ran over a period of eight months with measurements being made at four month intervals. Abalone behaviour was observed during the trials in the experimental tanks. Weight gain per abalone decreased with an increase in density for all tested size classes (5.04 ± 0.18 to 2.38 ± 0.17; 5.35 ± 0.21 to 4.62 ± 0.29; 7.97 ± 0.37 to 6.53 ± 0.28 g.abalone-1.month-1 for the 15-35, 45-65 and 70-90 g classes respectively, with an increased density of 16 to 24 %). Individual weight gain of 15-35 g abalone was similar at stocking densities of 16 % and 20 % while weight gain of 45-65 g and 70-90 g abalone decreased when density was increased above 16 %. Biomass gain (kg.basket-1.month-1) was not affected by stocking density in the 15-35 g and 45-65 g size classes (1.29 ± 0.02 and 0.97 ± 0.02 kg.basket-1.month-1 respectively). However, the biomass gained by baskets stocked with 70-90 g abalone increased with stocking density (1.08 ± 0.02 to 1.33 ± 0.02 kg.basket-1.month-1) with an increased density of 16 to 24 %) and did not appear to plateau within the tested density range (16 to 24 %). Food conversion ratio did not differ significantly between densities across all size classes. Stocking density did not have a significant effect on abalone condition factor or health indices. The proportion of abalone above the level of the feeder plate increased with density (7.26 ± 1.33 to 16.44 ± 1.33 with an increased density of 16 to 24 %). As a proportion of abalone situated in the area of the basket, the same proportions were situated on the walls above the feeder plate and on the feeder plate itself irrespective of stocking density (p > 0.05). Higher proportions of animals had restricted access to feed at higher stocking densities (p = 0.03). The amount of formulated feed available on the feeder plate did not differ between stocking densities throughout the night (p = 0.19). Individual abalone spent more time above the feeder plate at higher stocking densities (p < 0.05). The percentage of time above the feeder plate, spent on the walls of the basket and on the feeding surface was not significantly different at densities of 20 %, 22 % and 24 % (p > 0.05) but abalone stocked at 16 % spent a greater percentage of time above the feeder plate on the feeding surface (83.99 ± 6.26 %) than on the basket walls (16.01 ± 6.26 %). Stocking density did not affect the positioning of abalone within a basket during the day or at night. Different size H. midae are affected differently by increases in stocking density in terms of growth performance. Findings from this research may be implemented into farm management strategies to best suit production goals, whether in terms of biomass production or individual weight gain. The fundamental mechanisms resulting in reduced growth at higher densities are not well understood, however results from behaviour observations suggest that competition for preferred attachment space and feed availability are contributing to decreased growth rates. With knowledge of abalone behaviour at different densities, innovative tank designs may be established in order to counter the reduction in growth at higher densities.
Keywords: Haliotis midae -- South Africa; Haliotis midae fisheries -- South Africa; Abalones -- South Africa; Fish stocking -- South Africa; Abalone populations -- South Africa